2017
DOI: 10.21859/jrehab-180151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Structural Corrective and Respiratory Exercises on Cardiorespiratory Indices of Male Children Afflicted with Kyphosis

Abstract: Objective Structural deformities can impair different body functions, and kyphosis is one of the most common postural deformities. It seems that kyphosis induces unfavorable effects on the respiratory system. Impairment of pulmonary function, in turn, affects spirometer indices significantly. Some previous studies have indicated a positive influence of corrective structural exercise on kyphosis. Recently, respiratory muscle exercises were considered as one of the treatment methods of pulmonary disease. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Moghaddasi et al (23), addressing the effect of exercise on clinical manifestations of pulmonary function in asthmatic patients, reported that exercise could reduce symptoms of asthma (such as wheezing, dyspnea, and coughing) and improve pulmonary function. Meamari et al (24) examined the impact of six weeks of structural corrective exercises along with respiratory muscle exercises on cardiopulmonary indices in ten-year-old children with kyphosis. Consistent with the present study, they reported that respiratory exercises had increased FVC and FEV1 values.…”
Section: Discussionmentioning
confidence: 99%
“…Moghaddasi et al (23), addressing the effect of exercise on clinical manifestations of pulmonary function in asthmatic patients, reported that exercise could reduce symptoms of asthma (such as wheezing, dyspnea, and coughing) and improve pulmonary function. Meamari et al (24) examined the impact of six weeks of structural corrective exercises along with respiratory muscle exercises on cardiopulmonary indices in ten-year-old children with kyphosis. Consistent with the present study, they reported that respiratory exercises had increased FVC and FEV1 values.…”
Section: Discussionmentioning
confidence: 99%
“…When exhaling, they had to partly press their lips and contract the abdominal muscles, count to five, and exhale slowly through the mouth, counting from one to five. The intervention group performed this exercise three times during waking hours (at 12, 16, and 20 o'clock after the diaphragmatic breathing exercise) for 20 minutes (32,33).…”
Section: Samplingmentioning
confidence: 99%